Cognitive arousal assessment from central to peripheral nervous functions in school-age children - Nifareeda Samerphob; Dania Cheaha; Acharaporn Issuriya; Ekkasit Kumarnsit; Rodiya Manor (International Journal of Child Development and Mental Health, 2022)
Cognitive skills are a set of higher-order thinking processes that allow children to learn successfully. By developing cognitive skills, the brain is connected to Rapidly complete the information processes. The aim of this study was to examine the cognitive process development, decision making and eventually cognitive performance in school age children evaluated by the galvanic skin conductance response (SCR) method. Peripheral SCR signals during cognitive loading were recorded in children in grades 1 to 3 of a representative school in Southern Thailand. Eriksen flanker and dexterity tests were conducted to evaluate the development of its association with cognitive skill. Regression-based analyses showed reduced reaction time on Eriksen flanker (both congruent trials with regression coefficient = -0.02924, p <0.001 and incongruent trials with regression coefficient = -0.04231, p <0.001) and time spent to achieve dexterity tests (regression coefficient = -0.32206379, p <0.05) from students’ grades 1 to 3. In SCR modulation, analysis of variance revealed highest peak SCR magnitudes in students grade 3, compared to students in grade 2 (p <0.001) and grade 1 (p =0.046). On the other hands, numbers of peaks were highest in students grade 1 when they were in the calm stage (p <0.001), and highest in student grade 3 (p =0.002) when they were in the focus mind state. These findings support the association of the psychophysiological index of changes in brain and cognitive development among age related experience to focus attention improving under the task.